High-latitude thermospheric wind study using a Fabry-Perot interferometer at Tromsø in Norway:averages and variations during quiet times - Xu, H. (Heqiucen); Shiokawa, K. (Kazuo); Oyama, S.-i. (Shin-ichiro); Nozawa, S. (Satonori) (Springer Nature, 2019)
Abstract The average winds in the thermosphere during geomagnetically quiet times are important because they provide a baseline wind in the upper atmosphere, but they remain insufficiently understood at high latitudes. This paper reports the first direct ground-based wind measurements of the quiet-time thermospheric wind pattern at Tromsø in Norway using 2009–2015 data from a Fabry–Perot interferometer. We analyzed red-line wind measurements (630.0 nm; altitude: 200–300 km). On average, the zonal wind shows a decrease of eastward wind compared with diurnal tidal wind before midnight. A maximum speed of 100 m/s occurs at both the dusk and dawn sides. The meridional wind has a diurnal tide structure with a minimum value of − 130 m/s around midnight. We also found occasional large wind deviations (> 100 m/s) from the averages, even during geomagnetically quiet times. We suggest that these large wind deviations are caused by the plasma convection associated with weak substorm activities with auroral electrojet (AE) index values of less than 100 nT that occurred at local times different from that at Tromsø.